![a_(n)=a_(n-1)+(n-1)*4](https://img.qammunity.org/2023/formulas/mathematics/college/jjft4t212vwqkild3lhdu687u0grhtybq8.png)
1) To get to know the answer to this problem, we need to consider the first term 15 the common difference obtained by the difference between the terms:
![\begin{gathered} 19-15=4 \\ 23-19=4 \\ 27-23=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3qg101ijdnc52jbxn6kunt06nenh6vcd0m.png)
2) Therefore, we can write the recursive formula resorting to the previous term, i.e. our recursive formula is valid for the second term and so forth and so on.
![\begin{gathered} a_n=a_(n-1)+(n-1)d \\ \\ a_n=15+(2-1)4 \\ \\ a_2=15+4\Rightarrow a_2=19 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mwarbjiydfyum8ok9hcdcga6e5ebihclp8.png)
3) Thus, the answer is:
![a_n=a_(n-1)+(n-1)\cdot4](https://img.qammunity.org/2023/formulas/mathematics/college/8hw1g93ll6lp94f2ipwzioewsxy5tyanv0.png)